2017
DOI: 10.1044/2016_ajslp-16-0028
|View full text |Cite
|
Sign up to set email alerts
|

Does Naming Therapy Make Ordering in a Restaurant Easier? Dynamics of Co-Occurring Change in Cognitive-Linguistic and Functional Communication Skills in Aphasia

Abstract: This study was conducted to investigate the static and dynamic relationships between impairmentlevel cognitive-linguistic abilities and activity-level functional communication skills in persons with aphasia (PWA). Method: In Experiment 1, a battery of standardized assessments was administered to a group of PWA (N = 72) to examine associations between cognitive-linguistic ability and functional communication at a single time point. In Experiment 2, impairment-based treatment was administered to a subset of PWA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Moreover, it has been suggested that composite cognitive scores, such as those derived by the CLQT, are strongly associated with functional communication scores (Meier et al . ) and this was the case in our study. Further, the significant correlation between The Scenario Test UK and measures of praxis indicate a relationship between the ability to convey a message and the ability to gesture.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Moreover, it has been suggested that composite cognitive scores, such as those derived by the CLQT, are strongly associated with functional communication scores (Meier et al . ) and this was the case in our study. Further, the significant correlation between The Scenario Test UK and measures of praxis indicate a relationship between the ability to convey a message and the ability to gesture.…”
Section: Discussionsupporting
confidence: 80%
“…, Meier et al . ). Visuospatial skills are important when people with aphasia attempt to use alternative means of communication such as drawing or pictorial supports.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations